multiply the binomial ¡) 2a-9 and 3a+4
Answers
Answered by
179
(2a-9) (3a+4)
= 2a(3a+4) - 9(3a+4)
= 6a² + 8a - 27a - 36
= 6a² - 19a - 36
= 2a(3a+4) - 9(3a+4)
= 6a² + 8a - 27a - 36
= 6a² - 19a - 36
vinaykumar9:
thank you for your response
Answered by
4
Answer:
(2a - 9)(3a + 4) = 6a² - 19a - 36.
Step-by-step explanation:
We multiply the given binomials (2a -9) and (3a + 4)
(2a - 9) (3a + 4) = 2a(3a + 4) - 9(3a + 4)
=6a² + 8a - 27a - 36
= 6a²+(8a - 27a) - 36 (combining like terms)
= 6a² + a(8-27) -36
= 6a² - 19a -36
Therefore, (2a - 9)(3a + 4) = 6a² - 19a - 36.
Similar questions